Clearance in vulvar lichen sclerosus: a realistic treatment endpoint or a chimera?. (7th September 2017) - Borghi, A.; Virgili, A.; Minghetti, S.; Toni, G.; Corazza, M.
Abstract: Background: According to the current guidelines, the aim of vulvar lichen sclerosus (VLS) treatment was to improve symptoms and signs, not to cure. Objective: To assess (i) the rate of patients with VLS who achieved complete clearance of symptoms or objective features, or both, with a 12‐week pharmacological treatment and (ii) the predictive value of therapeutic response to the demographic and clinical features. Methods: We retrospectively included patients with VLS who had undergone any topical treatment for 12 weeks; demographics, history, VLS‐related symptoms and objective features recorded at baseline and on completion of treatment were collected and elaborated. The primary study endpoint was to assess the rate of patients achieving complete clearance of global subjective score (GSS), or in global objective score (GOS), and in both scores. Results: One hundred and ninety‐six patients were included; 24 (12.2%) were asymptomatic at baseline, and nine (4.6%) dropped out. After treatment, 78 patients (47.3%) achieved GSS = 0, 40 (21.4%) achieved GOS = 0, and 23 (13.9%) achieved complete clearance of both symptoms and signs. Lower symptom scores at baseline and shorter disease duration were associated with the achievement of symptom clearance at the end of the treatment. Earlier disease onset, diagnosis and beginning of study treatment as well as lower baseline GOS were significantly associated with complete recovery of VLS signs and clearance of both symptoms and signs. Conclusion: A relevant part of patients who undergo a 12‐week topical treatment is not completely cured of VLS. It may be hypothesized that these patients, in spite of a significant improvement, may still have substantial residual disease and, as a result, its effect on their quality of life.